Non alcoholic fatty liver disease: pathogenesis, role of (TNF-α, IL-6) in hepatic inflammation and future potential nutraceutical treatment - Safaa Ahmed Faheem; noha m. saeed; Reem N. El-naga; samar saad azab (Ain Shams University, 2019)
Non-alcoholic fatty liver disease (NAFLD) is a pathological condition characterized by the accumulation of triglycerides (TGs) in the hepatocytes and has usually been associated with hyperlipidemia, obesity, and insulin resistance. Besides, it is a progressive condition that has become one of the most common liver disorder in developed countries and is usually accompanied by increased cardiovascular and land liver disease mortality. NAFLD is a spectrum of liver disorders, progressing from simple steatosis to non-alcoholic steatohepatitis which is characterized by inflammation and hepatocellular injury then fibrosis which finally results in cirrhosis and even hepatocellular cancer. However, the molecular mechanism contributing to NAFLD progression is not fully understood. Its pathogenesis has usually been recognized by the "double-insult" hypothesis. the "first insult" includes accumulation of TGs in the hepatocyte, followed by a "second insult" where inflammatory mediators convince hepatocellular injury, inflammation, and fibrosis. In NAFLD, insulin resistance initiates the hepatic steatosis by different mechanisms. Furthermore, it was shown that NAFLD is associated with an inhibition of fatty acid oxidation in the mitochondria and an increase in the release of very-low-density lipoproteins. This review discusses the pathophysiology of NAFLD and the role of insulin resistance, obesity and inflammatory markers in the initiation of NAFLD. in addition to the different Therapeutic approaches for NAFLD.